Expression of Bacillus thuringiensis Toxin Affects the Leaf Anatomy of a Cotton Hybrid - Sundaramurthy, V. T. (International Journal of Bio-resource and Stress Management, 2023)
The transgenic cotton hybrids that carry an alien gene cry1Ac construct from Bacillus thuringiensis Berliner variety kurstaki is known to confer resistance to bollworm of cotton. But no information is known to science on the effects of the toxin produced by the alien gene on the anatomy of the leaf of transgenic cotton hybrid.Hence the light microscopic method was employed to investigate the effect of the alien gene on the leaf anatomy of a cotton hybrid. The alien gene cry1Ac toxin had altered the size of the various tissue components of the leaf of the transgenic cotton hybrid. The different cells of the leaf of the Bt-cotton hybrid had under gone varying degrees of reduction in size as compared to its conventional isogenic cotton hybrid. The accessory vascular bundle was present around the main vascular strands in the transgenic cotton hybrid with more number of xylem vessels. While it was absent in the conventional cotton hybrid. The density of stomata was two fold higher with increased sizes of guard cells and stoma on the adaxial surface of the leaf in the transgenic cotton hybrid as compared to the conventional cotton hybrid. These changes are considered as an adoptive mechanism to enhance the uptake of water and nutrients from the soils for enhanced synthesis of photosynthate to support its growth, yield of seed cotton and development of fibre.